Astrocytes underlie a faster-onset antidepressant effect of hypidone hydrochloride (YL-0919) - Li, Jin-Feng; Hu, Wen-Yu; Chang, Hai-Xia; Bao, Jin-Hao; Kong, Xiang-Xi; Ma, Hui; Li, Yun-Feng (Frontiers in Pharmacology, 2023)
Introduction: Major depression disorder (MDD) is a common and potentially life-threatening mental illness; however, data on its pathogenesis and effective therapeutic measures are lacking. Pathological changes in astrocytes play a pivotal role in MDD. While hypidone hydrochloride (YL-0919), an independently developed antidepressant, has shown rapid action with low side effects, its underlying astrocyte-specific mechanisms remain unclear. Methods: In our study, mice were exposed to chronic restraint stress (CRS) for 14 days or concomitantly administered YL-0919/fluoxetine. Behavioral tests were applied to evaluate the depression model; immunofluorescence and immunohistochemistry staining were used to explore morphological changes in astrocytes; astrocyte-specific RNA sequencing (RNA-Seq) analysis was performed to capture transcriptome wide alterations; and ATP and oxygen consumption rate (OCR) levels of primary astrocytes were measured, followed by YL-0919 incubation to appraise the alteration of energy metabolism and mitochondrial oxidative phosphorylation (OXPHOS). Results: YL-0919 alleviated CRS-induced depressive-like behaviors faster than fluoxetine and attenuated the number and morphologic deficits in the astrocytes of depressed mice. The changes of gene expression profile in astrocytes after CRS were partially reversed by YL-0919. Moreover, YL-0919 improved astrocyte energy metabolism and mitochondrial OXPHOS in astrocytes. Conclusion: Our results provide evidence that YL-0919 exerted a faster-onset antidepressant effect on CRS-mice possibly via astrocyte structural remodeling and mitochondria functional restoration.